1984
DOI: 10.1038/308645a0
|View full text |Cite
|
Sign up to set email alerts
|

The nature of endothelium-derived vascular relaxant factor

Abstract: The existence of endothelium-derived vascular relaxant factor (EDRF) was postulated by Furchgott and colleagues when they observed that acetylcholine paradoxically relaxed preconstricted aortic strip preparations by an endothelium-dependent mechanism. This phenomenon has since been demonstrated in different blood vessels and mammalian species and it can be elicited by several other agents. EDRF has been thought to be a humoral agent, a lipoxygenase derivative and possibly a free radical. In the study reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
207
1
12

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(237 citation statements)
references
References 17 publications
15
207
1
12
Order By: Relevance
“…It is unlikely that lack of penetration of hydroquinone into the tissue can account for its differentiation between exogenous and endogenous nitrate in the present study because it produced the expected reversal of EDRF/ NO-induced relaxations of rabbit aorta (Furchgott, 1984 (Colter & Quastel, 1950;Mittal et al, 1978;Martin et al, 1985;Laurence & Bennett, 1987 (Graser et al, 1990;Myers et al, 1990;Rubanyi et al, 1990), and it may be that a similar substance is liberated from the NANC nerves. Several physiologically-relevant Snitrosothiols have recently been shown to relax smooth muscle (Kowaluk & Fung, 1990) (Griffith et al, 1984) or as a generator of superoxide anions (Moncada et al, 1986). Our observations with SOD and with the chemiluminescent assay suggest that superoxide anion generation cannot explain the inhibitory effect of hydroquinone on NO in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that lack of penetration of hydroquinone into the tissue can account for its differentiation between exogenous and endogenous nitrate in the present study because it produced the expected reversal of EDRF/ NO-induced relaxations of rabbit aorta (Furchgott, 1984 (Colter & Quastel, 1950;Mittal et al, 1978;Martin et al, 1985;Laurence & Bennett, 1987 (Graser et al, 1990;Myers et al, 1990;Rubanyi et al, 1990), and it may be that a similar substance is liberated from the NANC nerves. Several physiologically-relevant Snitrosothiols have recently been shown to relax smooth muscle (Kowaluk & Fung, 1990) (Griffith et al, 1984) or as a generator of superoxide anions (Moncada et al, 1986). Our observations with SOD and with the chemiluminescent assay suggest that superoxide anion generation cannot explain the inhibitory effect of hydroquinone on NO in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…endogenous nitrate NANC system; indeed, such evidence would be necessary to establish NO as a neurotransmitter. Hydroquinone has been used frequently as an inhibitor of EDRF/NO relaxations of vascular smooth muscle (Furchgott, 1984) where it might act either as a free radical scavenger (Griffith et al, 1984) or as a generator of superoxide anions (Moncada et al, 1986). However, its effects on NANC responses have been less widely studied and results have been varied; Gillespie & Sheng (1990) found that hydroquinone produced a small reduction of NANC relaxations of the rat anococcygeus but had no effect on the bovine retractor penis.…”
Section: Introductionmentioning
confidence: 99%
“…It has, however, several properties in common with EDRF. For example, both relax the BRP (Gillespie & Sheng, 1988a,b), both increase cyclic GMP (Rapoport & Murad, 1983;Diamond & Chu, 1983;Bowman & Drummond, 1984), both are abolished by anoxia (Furchgott & Zawadzki, 1980;Bowman & McGrath, 1985) and by borohydride (Griffith et al, 1984;Gillespie & Sheng, unpublished observation), as well as by haemoglobin. If EDRF is nitric oxide, it is possible that the NANC transmitter is also nitric oxide.…”
Section: Introductionmentioning
confidence: 99%
“…The endothelium-dependent relaxation of arterial Zawadski, 1980;Griffith et al, 1984), identical with smooth muscle which can be induced by a wide or closely related to nitric oxide (Ignarro et al, 1987; variety of compounds such as acetylcholine (ACh), is Palmer et al, 1987;Furchgott, 1988), and is avidly mediated by stimulated release of endotheliumbound by haemoglobin (Kelm et al, 1988). derived relaxing factor (EDRF).…”
Section: Introductionmentioning
confidence: 99%